Phase I study of emactuzumab single agent or in combination with paclitaxel in patients with advanced/metastatic solid tumors reveals depletion of immunosuppressive M2-like macrophages. (22nd May 2019) - Gomez-Roca, C A; Italiano, A; Le Tourneau, C; Cassier, P A; Toulmonde, M; D'Angelo, S P; Campone, M; Weber, K L; Loirat, D; Cannarile, M A; Jegg, A -M; Ries, C; et al.
Abstract: Background: Emactuzumab is a monoclonal antibody against the colony-stimulating factor-1 receptor and targets tumor-associated macrophages (TAMs). This study assessed the safety, clinical activity, pharmacokinetics (PK) and pharmacodynamics (PD) of emactuzumab, as monotherapy and in combination with paclitaxel, in patients with advanced solid tumors. Patients and methods: This open-label, phase Ia/b study comprised two parts (dose escalation and dose expansion), each containing two arms (emactuzumab, every 2 or 3 weeks, as monotherapy or in combination with paclitaxel 80 mg/m 2 weekly). The dose-escalation part explored the maximum tolerated dose and optimal biological dose (OBD). The dose-expansion part extended the safety assessment and investigated the objective response rate. A PK/PD analysis of serial blood, skin and tumor biopsies was used to explore proof of mechanism and confirm the OBD. Results: No maximum tolerated dose was reached in either study arm, and the safety profile of emactuzumab alone and in combination does not appear to preclude its use. No patients receiving emactuzumab monotherapy showed an objective response; the objective response rate for emactuzumab in combination with paclitaxel was 7% across all doses. Skin macrophages rather than peripheral blood monocytes or circulating colony-stimulating factor-1 were identified as an optimal surrogate PD marker to select the OBD. Emactuzumab treatment alone and in combination with paclitaxel resulted in a plateau of immunosuppressive TAM reduction at the OBD of 1000 mg administered every 2 weeks. Conclusions: Emactuzumab showed specific reduction of immunosuppressive TAMs at the OBD in both treatment arms but did not result in clinically relevant antitumor activity alone or in combination with paclitaxel. (ClinicalTrials.gov Identifier: NCT01494688)